Pembangunan Pariwisata Kulon Progo Melalui Konsep Green Economy dan Blue Economy - Wiratma, Harits Dwi; Nurgiyanti, Tanti (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2019)
The development of the tourism sector is carried out massively, because this sector is one of the biggest foreign exchange earners after oil palm in Indonesia. Each local government competes one another to improve in the competitiveness of its tourism sector, like Kulon Progo district. The massive development in this sector is feared to have environmental impacts. Environmental support in tourism development also needs concern. Green Economy and Blue Economy concept is expected to provide solutions both in terms of tourism industry or sustainable development for the tourism sector, because the environment becomes part of tourism development.